Emergency remote teaching in the Covid-19 Pandemic Context: Reports of a challenging and successful experience in an Undergraduate Chemistry class at IFRN (Research, Society and Development, 2021)
This article aims to describe and report the experience lived in emergency remote education (ERE), during module I of a total of six modules, from the perspective of the students' perspective, leading them to reflect on teacher training and challenges for education in the 21st century. The present research has a qualitative nature, showing the social quality, and the descriptive type, which in the educational scope, privileges the process to the detriment of the final product. It took place with 17 students from the 1st semester of the degree course in Chemistry at IFRN located in the interior of the state of Rio Grande do Sul, and the virtual learning environment used is Google Classroom. Despite the limitations, the students surveyed revealed more successful experiences and exceeded expectations regarding the new teaching format and demonstrated good acceptance, which leads us to reflect on the perspective of developing teaching activities in the virtual learning environment even during classroom teaching. , in the format that they call hybrid education, which integrates part of the activities developed to the remote format. This experience shows that a laboratory to study and apply digital tools combined with teaching in an investigative approach is feasible and opens up new possibilities with a view to improving teacher training and, consequently, teaching in the medium and long term.